Dampak Mengkonsumsi Minuman Keras Pada Kalangan Remaja - Khaylla Dena Aprellia; Muhammaad Ardi Purwanto; Nur Kartika Putri; Shellyn Dwi Agatha; Liss Dyah Dewi A (Jurnal Kajian dan Penelitian Umum, 2024)
The aims of this study were: 1) to describe the impact of alcohol on the lives of adolescents in Lamoluo Village, West Wawonii District, Konawe Islands Regency. 2) to explain the efforts made in tackling adolescents who consume liquor in Lamoluo Village, West Wawonii District, Konawe Islands Regency. The type of research used is research with qualitative analysis. The subjects of this study consisted of 5 people consisting of 3 teenagers as respondents 1 unscrupulous health workers 1 unscrupulous Konawe Islands Police as informants. The results of this study indicate that the impact of consuming liquor in Lamoluo Village, West Wawonii District, Konawe Islands Regency, namely that it will make drunkenness bring about changes in men's physical health, the impact of drinking among adolescents is not good for the people around them, causing adolescents to tend to be sensitive to emotional anger, easy to calm disturbed mind, causing fights, restless, hot, unconscious, often makes a mess, drives a motorcycle recklessly, shouts disturbing community competition. Efforts made in tackling teenagers consuming liquor. Carrying out religious education efforts, conducting household coaching, conducting socialization, carrying out outreach efforts for law and order and security.